UPAYA MENINGKATKAN MUTU PEMBELAJARAN MELALUI PENERAPAN SUPERVISI AKADEMIK DI SD NEGERI SUKAMAJU 1 KOTA CIMAHI - Mutiah, Enung; Anugrah, Muhamad (Universitas Islam Balitar, 2021)
The purpose of this study is to find alternative solutions to problems in improving the quality of learning through the application of academic supervision. Classroom action research is focused on the learning process using the School Action Research method. The action taken in the research is the implementation of academic supervision by the principal. The provision of academic supervision provided by the principal will increase the quality of teacher learning in the classroom. The results showed that 1) In general, there was an increase in the quality of learning starting from pre-cycle, cycle 1, and cycle 2. Where in the pre-cycle the quality of learning was at an average value of 77,31, then increased to 81.38 in cycle 1 , and became 85,18 in cycle 2. The researcher's suggestion is that academic supervision should be more supported by the provision of adequate facilities and infrastructure. Teachers should be more creative in learning and learning assessment, because it can be seen from research that the learning process and learning assessment are the main things in improving the quality of learning.